2018
DOI: 10.1002/glia.23560
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical stress originates in the rat optic nerve head during development of autoimmune optic neuritis

Abstract: Optic neuritis is a common manifestation of multiple sclerosis, an inflammatory demyelinating disease of the CNS. Although it is the presenting symptom in many cases, the initial events are currently unknown. However, in the earliest stages of autoimmune optic neuritis in rats, pathological changes are already apparent such as microglial activation and disturbances in myelin ultrastructure of the optic nerves. αB‐crystallin is a heat‐shock protein induced in cells undergoing cellular stress and has been report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 41 publications
2
8
1
Order By: Relevance
“…7d). Previous studies have also reported RGC loss prior to inflammatory infiltration, demyelination, or edema of the optic nerve [17, 55–57]. In line with reports by other authors [3], we found that early signs of RGC pathology precedes IRL thinning, suggesting that neuronal damage may occur, at least partially, independent of apparent inflammation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…7d). Previous studies have also reported RGC loss prior to inflammatory infiltration, demyelination, or edema of the optic nerve [17, 55–57]. In line with reports by other authors [3], we found that early signs of RGC pathology precedes IRL thinning, suggesting that neuronal damage may occur, at least partially, independent of apparent inflammation.…”
Section: Discussionsupporting
confidence: 92%
“…Our study lacked a CFA-only control group to assess whether the effects of neuro-axonal degeneration observed are MOG-specific. However, previous studies assessing optic nerve and retinal pathology in autoimmune ON reported little to no difference between the CFA-only group and healthy controls in inflammatory pathology and neuro-axonal degeneration [2, 57]. Our results suggests that IRL changes in EAE are primarily influenced by pRNFL changes over time; yet previous OCT studies investigating pRNFL changes in EAE mice report contradictory findings [3, 32].…”
Section: Discussioncontrasting
confidence: 62%
“…It has been shown that in ammatory responses play an important role in the development of ON (30), and optic nerve demyelination and in ltration have also been found to correlate with the severity of clinical disease in EAE mice (31). Among in ammatory cells, activated macrophages and microglia are the major cell types in ON that are closely associated with demyelination, axonal damage and loss of visual function (32).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that inflammatory responses play an important role in the development of ON (29), and optic nerve demyelination and infiltration have also been found to correlate with the severity of clinical disease in EAE mice (30). Among inflammatory cells, activated macrophages and microglia are the major cell types in ON that are closely associated with demyelination, axonal damage and loss of visual function (31).…”
Section: Discussionmentioning
confidence: 99%